Assessment of left Ventricular Longitudinal Function in Different Hypertensive Left Ventricular Geometry (University Heart Journal, 2020)
Background: Hypertension remains as the major risk factor for cardiovascular diseases. Hypertensive left ventricular hypertrophy was shown to be associated with increased morbidity and mortality. Left ventricular radial function (Ejection fraction) tends to remain normal in hypertensive patients, particular attention should be given to longitudinal function along with diastolic function. Left ventricular longitudinal function may vary across different hypertensive LV geometry with different prognosis.Results: Of the total 214 study subjects, 109 (50.9%) were Cases and 105 (49.1%) were Controls. The mean ages of cases and controls were 52.66 (± 10.96) and 50.21 (± 10.91) years respectively. Left ventricular ejection function (LVEF) was almost identical in both groups [mean LVEF in case 68.7 % (± 6.9) Vs control 68.7(± 5.4), (p 0.947)]. Among the cases 43% had concentric hypertrophy (CH), 20% had eccentric hypertrophy (EH), 20% had concentric remodeling (CR), while normal geometry constituted the least 16.5%. Mean systolic mitral annular velocity (Vs) and mean early diastolic velocity (Ve) assesed by pulse wave tissue doppler imaging were observed to be significantly decreased in cases compared to their control counterpart (11.46 ± 1.26 vs. 15.41 ± 1.00 cm/sec, p < 0.001 and 13.80 ± 2.37 vs. 16.76 ± 2.67 cm/sec, p < 0.001. There was significant reduction of Vs in concentric hypertrophy and eccentric hypertrophy (11.31 ± 1.41 and 12.27 ± 2.14). (p